2020
DOI: 10.25077/jsfk.7.1.15-22.2020
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Outcome Klinis Berdasarkan Kualitas Hidup dan Biaya Medik Langsung Pasien Diabetes Melitus Tipe 2

Abstract: Diabetes Melitus (DM) tipe 2 merupakan penyakit kronis yang membutuhkan terapi untuk mengontrol glukosa darah. Pengontrolan glukosa darah yang buruk berdampak pada penurunan kualitas hidup dan peningkatan biaya. Tujuan penelitian adalah menganalisis perbedaan outcome klinis yaitu kadar Glukosa Darah Sewaktu (GDS) selama 3 bulan berdasarkan kualitas hidup dan biaya medis langsung. Outcome klinis dikatakan terkontrol apabila GDS <200 mg/dL dan tidak terkontrol apabila GDS ≥200 mg/dL. Rancangan penelitian ini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…From the duration of type 2 diabetes mellitus, the most patients are patients with a duration of more than 5 years (52,22%). The prevalence of the duration of patients suffering from type 2 diabetes mellitus is in accordance with previously conducted research which states that the prevalence of type 2 diabetes mellitus duration is most prevalent in the group of more than 5 years (Ratnasari, Andayani, & Endarti, 2020). Diabetes mellitus is a degenerative disease that requires lifelong treatment (Soelistijo, 2021).…”
Section: Results and Discussion (A) Patient Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…From the duration of type 2 diabetes mellitus, the most patients are patients with a duration of more than 5 years (52,22%). The prevalence of the duration of patients suffering from type 2 diabetes mellitus is in accordance with previously conducted research which states that the prevalence of type 2 diabetes mellitus duration is most prevalent in the group of more than 5 years (Ratnasari, Andayani, & Endarti, 2020). Diabetes mellitus is a degenerative disease that requires lifelong treatment (Soelistijo, 2021).…”
Section: Results and Discussion (A) Patient Characteristicssupporting
confidence: 87%
“…In previous studies, the largest components of medical expenditure related to diabetes complications were cardiovascular disease (42.3% of total complication costs), nephropathy (23%) and eye complications (14%) (Javanbakht et al, 2011). In another study, it was stated that patients who showed uncontrolled clinical outcomes (64.5%) with average direct medical costs incurred by patients were IDR 489.005, and for controlled clinical outcomes showed better quality of life and lower costs (Ratnasari et al, 2020). To evaluate the effectiveness of type 2 diabetes mellitus treatment therapy, an economic evaluation based on cost and clinical parameters is needed.…”
Section: Introductionmentioning
confidence: 96%
“…Dari durasi diabetes mellitus tipe 2, paling banyak adalah pasien dengan durasi lebih dari 5 tahun. Prevalensi durasi pasien menderita diabetes mellitus tipe 2 ini sesuai dengan penelitian yang sebelumnya dilakukan yang menyatakan bahwa prevalensi durasi diabetes mellitus tipe 2 paling banyak terjadi pada kelompok lebih dari 5 tahun [20]. Penyakit diabetes mellitus merupaka penyakit degeneratif yang memerlukan pengobatan seumur hidup [17].…”
Section: Hubungan Sosiodemografi Pasienunclassified
“…Beberapa penelitian menyebutkan bahwa kombinasi antidiabetik banyak digunakan pada pengobatan DM tipe 2. Pemberian antidiabetik disesuaikan dengan kondisi dan kebutuhan pasien sesuai algoritma terapi DM tipe 2, mulai dari monoterapi kemudian dilanjutkan dengan kombinasi antidiabetik [15]. Jumlah obat yang diresepkan tergantung pada kondisi klinis pasien.…”
Section: Karakteristik Pasienunclassified